Sistem Pembayaran Berbasis Web Menggunakan Sensor RFID Melalui Software Processing Di Kab Bireuen - T. Irfan Fajri; Muazziss Najmi; Muhammad Rizki Aulia (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2021)
This study aims to create a parking payment system that is easier to use, users do not need to use cash for the payment process and overcome queues that often occur at the parking gate and also make it easier for the manager to manage parking payments. The method used in this re-search is Literature Study, Field study where in the field study requires hardware and software. This research was carried out at Suzuya Mall Bireuen using a qualitative method where the system was created to facilitate the parking payment process, where users simply use an inte-grated RFID tag card and have been given a balance to make the payment process so that the payment process does not need to use cash and can overcome the queue in the parking lot, in this case the user can also refill the balance so that the balance in the RFID tag card can in-crease and can be reused for payment processing